(untitled) (Contemporary Journal of Social Science Review, 2026)
The interaction of artificial intelligence (AI), global economic interdependence, and foreign policy is turning into one of the issues of modern international politics. AI has ceased to be just a technological innovation in the context of a multipolar world where the United States, China, the European Union, Russia, and the emergent regional powers engage in strategic competition. It is becoming a geopolitical tool that defines trade, finance, supply chains, surveillance abilities, and diplomatic bargaining power. The thesis of this paper is that AI enhances the weaponization of economic interdependence through states being able to monitor, predict, manipulate, and disrupt transnational network with unprecedented accuracy. The paper examines how AI is reshaping economic relationships between countries based on international political economy and foreign policy theory, which are previously sources of mutually beneficial relations, into instruments of coercion. It also studies how states can adjust their foreign policies to this fact by focusing on resilience, technological sovereignty, strategic decoupling and coordination through alliances. The paper finds that AI is redefining foreign policy in a multipolar world by making the line between economic cooperation and strategic vulnerability indistinct, and driving the states to reconsider interdependence not as the source of peace, but as a battlefield of power.